Development of a walkability index from the 15-minute city perspective - Silva, Aryelle Nayra Azevedo; Silva, Luiz Bueno da (Technical and Scientific Journal Green Cities, 2025)
Pedestrian-centered urban planning has been gaining notoriety among researchers and public policy makers immersed in the debate on sustainability and health. To assess how inviting an urban space is to pedestrians, a walkability index is generally used. The first indices appeared in the 90s, however, there is currently no consensus on which would be the most accurate or best tool to evaluate each scenario, which implies the continuous emergence of new methodologies. Therefore, this article aims to contribute to the advancement of literature through the development of a walkability index from the perspective of the 15-minute city. For this purpose, a review of the literature on walkability indices was carried out, to better support the construction of the tool. Subsequently, the walkability index is structured, with 30 indicators divided into 5 categories: pedestrian infrastructure, aesthetics and comfort, diversity (15-minute city), safety and mobility. This research is of important social relevance, where results obtained can represent a great contribution to researchers in the area, urban managers and society in general, since an accurate diagnosis of walkability is the first step towards conducting more assertive improvements to pedestrian infrastructure.